Categorization of methods used in cost–effectiveness analyses of vaccination programs based on outcomes from dynamic transmission models. (June 2012) - Mauskopf, Josephine; Talbird, Sandra; Standaert, Baudouin
The aim of this study is to categorize methods used to estimate the cost–effectiveness of vaccination programs using dynamic transmission models, and assess value to decision-makers. A targeted literature search of PubMed has been carried out for this purpose. A review of 43 articles presenting cost–effectiveness analyses of vaccination programs based on dynamic transmission models identified four methods for the estimation of a cost–effectiveness ratio: cumulative population values over a fixed time horizon; population values for a steady-state year; cohort values from time of program initiation; and cohort values at steady state. Cost–effectiveness estimates are sensitive to the choice of time horizon or number of cohorts included. Estimates at steady state are the most comparable to estimates for other healthcare interventions but do not account for pre-steady-state periods. Population values provide estimates of budget impact. In conclusion, four different methods were identified for converting clinical outcomes from a dynamic transmission model to cost–effectiveness estimates. Sensitivity analyses for time horizon or number of cohorts considered should be routinely performed.